BS EN 14587-2. Railway applications. Infrastructure. Flash butt welding of rails. Part 2. New R200, R220, R260, R260Mn, R320Cr, R350HT, R350LHT, R370CrHT and R400HT grade rails by mobile welding machines at sites other than a fixed plant (23rd June 2021) - British Standards Institution,
No abstract available